PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP OPINI AUDIT TERKAIT GOING CONCERN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2015 – 2017) - Felix Irwanto, Hendang Tanusdjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to examine the effect of profitability, liquidity, and solvency ratios on audit opinions related to going concern received by the company. This research uses secondary data; manufacturing companies listed on the Indonesia Stock Exchange in 2015 - 2017. The research samples contained in this study were 168 companies. The sampling method is purposive sampling. The profitability variable is measured by the Return on Assets ratio, the liquidity variable is measured by the Current Ratio, and the measurement of the solvency variable by the Debt to Assets ratio. These ratios are calculated using company financial data contained in the financial statements listed on the Indonesia Stock Exchange. The sample criteria determined in the study are companies that suffered losses during the period 2015 - 2017, manufacturing companies that published financial statements in Rupiah and companies that did not merge. The results showed that profitability had a negative effect, liquidity had no effect and solvency had a positive effect on audit opinions related to going concern. Profitability, liquidity and solvency simultaneously influence audit opinion regarding going concern.